INTEGRATING MATHEMATICS LEARNING AND FINANCIAL LITERACY THROUGH A CONTEXTUAL APPROACH IN ELEMENTARY SCHOOLS - Tamarin, Vina; Samsul Solihin Saleh, Muhammad (EMTEKA: Jurnal Pendidikan Matematika, 2025)
This article is a narrative–systematic literature review that clarifies how financial literacy is integrated into elementary mathematics through a contextual approach. Conducted qualitatively, it synthesizes studies from 2015–2025 obtained from ERIC, DOAJ, Google Scholar, Garuda, and Sinta databases using clear inclusion and exclusion criteria. Integration targets specific areas of financial literacy such as budgeting, saving, discounts and percentages, price comparison, simple interest, and distinguishing needs from wants all mapped to number, fraction, ratio, and percentage concepts. Findings reveal that this integration enhances students' engagement, accuracy in calculating percentages or discounts, and their decision-making in financial contexts. Grounded in constructivism and the CTL framework (inquiry, modeling, questioning, learning community, reflection, and authentic assessment), this approach strengthens numeracy and financial behavior simultaneously. The contextual model provides practical, low-resource, and time-efficient learning activities relevant to students' real lives, serving as a practical foundation for curriculum development.